A new procedure for preparation of Sulfon-Z compounds. - H. K. Al- Daraji , Alaa (University of Thi-Qar Journal of Science, 2012)
Four compounds (Sulfon – Z) were prepared by a new procedure where Z is; N, S, O, and relatingmoieties. This procedure have many advantages comparing with other methods, its simple and easy, short time for preparation process (45 minutes in maximum), available starting materials (such as compounds; A,B, C, and others), cheap, relativily high percentage yield ( 60 – 96 %). However, above points are depending on the nature of starting materials. The products were identified by; melting point, thin- layer chromatography technique and Infra-red spectra. In addition, biological activity of these compounds have been studied against three different species (St.aureus, E . coli and Candida albicans